1995
DOI: 10.1063/1.113680
|View full text |Cite
|
Sign up to set email alerts
|

Carrier confinement by multiple quantum barriers in 1.55 μm strained GaInAs/AlGaInAs quantum well lasers

Abstract: Carrier confinement performance by multiple quantum barriers (MQB) is demonstrated in 1.55 μm strained GaInAs/AlGaInAs multiple quantum well (MQW) lasers grown by molecular beam epitaxy. The strained MQW lasers with MQB at p-side optical confinement layer show larger characteristic temperature and slope efficiency at high temperature than those without MQB. It is also shown that the MQW lasers with MQB have less spontaneous emission from the optical confinement layer than the lasers without MQB. As another imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The MQB was calculated [7,8] and is a useful structure for elevating the performance of the red and infrared LEDs and LDs [9][10][11]. In contrast to the previously reported photoluminescence (PL) result that the reduction of the nonradiative effect in the sample will enhance the PL intensity, the substantial reduction of the capture rate of the MQW will reduce the EL intensity and lead to higher energy band emission at low temperature.…”
Section: Introductionmentioning
confidence: 98%
“…The MQB was calculated [7,8] and is a useful structure for elevating the performance of the red and infrared LEDs and LDs [9][10][11]. In contrast to the previously reported photoluminescence (PL) result that the reduction of the nonradiative effect in the sample will enhance the PL intensity, the substantial reduction of the capture rate of the MQW will reduce the EL intensity and lead to higher energy band emission at low temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Since the mobility of electron is higher than that of hole, MQB structure is usually used at the p-type guiding layer as an electron barrier for longwavelength laser. 4,5 As compared with the conventional stepindex separate confinement heterostructure ͑SCH͒ laser, significant reduction of spontaneous emission from the guiding layer for the laser with MQB is observed, indicating the enhanced electron confinement by MQB. The resultant longer electron escape time is also beneficial for high speed modulation.…”
Section: Suppression Of Electron and Hole Leakage In 13 M Algainas/imentioning
confidence: 93%
“…The resultant longer electron escape time is also beneficial for high speed modulation. 4 Recently, it is found that hole injection into the n-type guiding can be significant above 360 K for 1.3 m InGaAsP/InP multiple quantum well ͑MQW͒ lasers. Consequently, the temperature dependence of slope efficiency is increased rapidly.…”
Section: Suppression Of Electron and Hole Leakage In 13 M Algainas/imentioning
confidence: 99%
“…In order to overcome the carrier a) Electronic mail: neete@mail.cgu.edu.tw leakage problem and improve the external quantum efficiency and carrier confinement, it is very effective to increase the effective heterobarrier by utilizing the enhanced electron wave confinement by novel multiquamtum barriers (MQBs). [4][5][6] In this letter, the enhanced carrier confinement effect of MQBs in InGaN/GaN LEDs is demonstrated, by observing the temperature-dependent characteristics of electroluminescence (EL) measurements. With decreasing the lattice temperature, anomalously decreased EL intensity of the InGaN active layer has been observed for both diodes accompany with the appearance of the Mg-doped GaN transition 7, 8 at lower temperature below 200 K. The rate equation models are invoked to corroborate the abnormal temperature behaviors of the EL intensity and the dramatic differences of radiative recombination zone shifts between the LEDs with and without MQBs.…”
Section: Introductionmentioning
confidence: 98%